Progress in development and applications of cherenkovtype detectors for fast electron studies in tokamaks - Rabinski, M.; Jakubowski, L.; Malinowski, K.; Mirowski, R.; Sadowski, M.J.; Zebrowski, J. (Вопросы атомной науки и техники, 2011)
The paper presents advance in a new method developed in the Institute for Nuclear Studies (IPJ) for direct detection
of high-energy (super-thermal, runaway) electrons generated in tokamaks. The technique in question is based on
registration of the Cherenkov radiation, emitted by energetic electrons, moving through a transparent medium (radiator
body) with a velocity higher than the velocity of light in this material. The main aim of the presented studies was to
develop a diagnostic technique applicable for investigation of fast electron beams within magnetic confinement fusion
(MCF) facilities. Представлено досягнення нового методу, розробленого в Інституті ядерних досліджень(ИЯД) для прямої реєстрації високоенергетичних (надтеплових, втікаючих) електронів, генеруємих у токамаках. Технічно задача заснована на реєстрації черенковського випромінювання, що випускається енергетичними електронами, які рухаються через прозоре середовище(випромінювальне тіло) зі швидкістю вище швидкості світла в даному матеріалі. Основною метою представлених досліджень була розробка діагностичної методики, застосованої для вивчення швидких електронних пучків у термоядерних магнітних пастках(ТМП). Представлены достижения нового метода, разработанного в Институте ядерных исследований (ИЯИ) для прямой регистрации высокоэнергетических (надтепловых, убегающих) электронов, генеруємых в токамаках. Технически задача основана на регистрации черенковского излучения, испускаемого энергитичными электронами, движущимся через прозрачную среду(излучательное тело) со скоростью выше скорости света в данном материале. Основной целью представленных исследований была разработка диагностической методики, применимой для изучения быстрых электронных пучков в термоядерных магнитных ловушках(ТМЛ).